Rare nonsyndromic multiple supernumerary and permanent impacted teeth in a young female patient: A case report - El Mehdi Hariri; Mohamed Sellouti; Hind Ramdi (Radiology Case Reports)
Teeth, either erupted or impacted, that exceed the normal count are known as supernumerary teeth. They can appear unilaterally or bilaterally, singly or in multiples, and may be located anywhere in both dental arches. Multiple permanent impacted supernumerary teeth are uncommon and are often associated to syndromes but can be idiopathic. The prevalence of nonsyndromic multiple supernumerary teeth is under 1%. Here, we present a rare case of nonsyndromic multiple supernumerary and permanent impacted teeth in a young female patient, who reported with no loss of deciduous teeth and no eruption of permanent teeth except the first maxillary and mandibular permanent molars. A panoramic radiograph showed several supernumerary and permanent impacted teeth in both maxillary and mandibular arches. The diagnosis of idiopathic hyperdontia was made on the basis of clinical features and radiographic examination, and the management strategy needs to be planned with a multidisciplinary approach.